50 simple things you can do to save the earth (Earthworks Press, 1989)
The book introduces environment issues such as greenhouse effect, nitrogen oxide, ultraviolet as well as warns of endangerous in groundwater, acid rain, landfills. The book offers more than 50 suggestions for concerned people who want to take an active role in saving the planet